2017
DOI: 10.1007/s12033-017-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Expression of Recombinant Proteins and Abundance of H3K4Me3 on the Enhancer of Human Cytomegalovirus Major Immediate-Early Promoter

Abstract: Role of epigenetic regulation in the control of gene expression is well established. The impact of several epigenetic mechanisms, such as DNA methylation and histone acetylation, on recombinant protein production in mammalian cells has been investigated recently. Here we investigate the correlation between the selected epigenetic markers and five trastuzumab biosimilar-producing Chinese hamster ovary (CHO) cell lines in which the expression of trastuzumab is driven by human cytomegalovirus (HCMV) major immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown correlations between activating or repressive histone modifications associated with the major IE gene and the levels of viral gene expression. For example, association of the MIEP with H3K4me2, H3K4me3, H3K9/14ac, H3S10ph or H4Kac has been linked to high levels of IE (or transgene) transcription and productive infection or reactivation from latency [72,[110][111][112][113][114][115][116][117][118][119][120]. By contrast, the presence of H3K9me2, H3K9me3 or H3K27me3 at the MIEP generally correlates with low levels of IE transcription and either latent or the onset (pre-IE phase) of productive infection [110][111][112]115,116] ( Figure 1).…”
Section: Transcriptional Control Of the Major Ie Genementioning
confidence: 99%
“…Numerous studies have shown correlations between activating or repressive histone modifications associated with the major IE gene and the levels of viral gene expression. For example, association of the MIEP with H3K4me2, H3K4me3, H3K9/14ac, H3S10ph or H4Kac has been linked to high levels of IE (or transgene) transcription and productive infection or reactivation from latency [72,[110][111][112][113][114][115][116][117][118][119][120]. By contrast, the presence of H3K9me2, H3K9me3 or H3K27me3 at the MIEP generally correlates with low levels of IE transcription and either latent or the onset (pre-IE phase) of productive infection [110][111][112]115,116] ( Figure 1).…”
Section: Transcriptional Control Of the Major Ie Genementioning
confidence: 99%
“…Methylation of H3K4 and phosphorylation of serine 10 of H3 (H3S10ph) are also characteristic of transcriptional activation [154,155]. Thus, it is unsurprising that H3K4me2, H3K4me3, H3K9/14ac, H3S10ph, and H4Kac recruitment to the MIE locus results in increased gene transcription from this region ( Figure 2) [48,49,[131][132][133][134][135]156,157], suggesting these modifications render this enhancer/promoter more accessible to transcription factors that promote active transcription. Histone acetyltransferases (HATs; e.g., KAT6A/MOZ) and demethylases (e.g., KDM1A/LSD1, KDM4A/JMJD2, KDM6B/JMJD3) activate the MIE locus by adding acetyl groups and removing methyl groups from histones at the MIE enhancer region [140], which is necessary for transcription initiation from this locus during reactivation.…”
Section: Activation Of the Mie Locus By Histone Ptmsmentioning
confidence: 99%
“…To avoid this, genetic sequences that maintain an open chromatin configuration have been used [195,196]. Direct silencing of the CMV promoter used for most transgenes, either by DNA-methylation or by changes in the histone modifications has also been shown [197][198][199][200]. These different strategies to silence the gene of interest are most likely due to the cell's drive to remove the stress of high productivity [201][202][203], by which ever means possible.…”
Section: Maintaining Stabilitymentioning
confidence: 99%